Performance Pay and Multidimensional Sorting: Productivity, Preferences, and Gender - Dohmen, Thomas; Falk, Armin (American Economic Review, 2011)
This paper studies the impact of incentives on worker self-selection in a controlled laboratory experiment. Subjects face the choice between a fixed and a variable payment scheme. Depending on the treatment, the variable payment is a piece rate, a tournament, or a revenue-sharing scheme. We find that output is higher in the variable-payment schemes compared to the fixed-payment scheme. This difference is largely driven by productivity sorting. In addition, different incentive schemes systematically attract individuals with different attitudes, such as willingness to take risks and relative self-assessment as well as gender, which underlines the importance of multidimensional sorting. (JEL C91, D81, D82, J16, J31)